The Effect of Nutritional Education Using Cognitive Approaches and Psychomotor Approaches on Fruit and Vegetable Consumption Behavior in Children - Anggraini, Fritria Dwi; Nisa, Fauziyatun; Hasina, Siti Nur; Munjidah, Annif (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: One of the problems related to eating behavior in children less than 5 years is the lack of consumption of fruits and vegetables. With this problem, an approach is needed to better consume it. AIM: This study aims to determine the effect of nutritional education using cognitive approaches (using illustrated storybooks and puppet shows) and psychomotor approaches (using puzzle and fruit and vegetable cards) on fruit and vegetable consumption behavior in children in the An-Nur Surabaya Kindergarten. METHODS: This study used a quasi-experimental study with a pre- and post-test group. The population is 48 respondents. Sampling uses the Probability sampling method with simple random sampling. The independent variable was nutrition education using media illustrated storybooks media, puppet shows, puzzles, and fruit and vegetable cards, meanwhile the dependent variable is consumption behavior of fruits and vegetables. The intervention was carried out 4 times. FFQ form was used to assess fruit and vegetables consumption behavior. RESULTS: The results showed that the average consumption of fruits and vegetables before the intervention was 168 g or equivalent to 1 portion, and the average after intervention was 304 g or equivalent to 3 servings. There is a significant influence (p = 0.000) on fruit and vegetable consumption through nutritional education. CONCLUSION: Nutritional education using media should be accompanied by a commitment to increase children’s motivation in eating fruits and vegetables.